Compact: Building Employee Loyalty at Lingkar Coffee Shop through Leadership Style, Work Motivation, and Work Environment (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2025)
This study aims to analyze the influence of leadership style, work motivation, and the work environment on employee loyalty at Coffee Shop Lingkar in Semarang City. The background of this study stems from the phenomenon of fluctuating employee loyalty levels, characterized by staff turnover within a certain period. The research method used a quantitative approach with census sampling, with the entire population of 36 employees being sampled. Data were collected through a Likert-scale questionnaire and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) using the SmartPLS 4 application. The results show that leadership style has a positive and significant effect on employee loyalty. Work motivation also proved to have a positive and significant effect and was the dominant factor influencing loyalty. Furthermore, the work environment had a positive and significant effect, although its influence was less significant than the other variables. Overall, these three variables explained 82.4% of employee loyalty, with the remainder influenced by factors outside this study. This research provides a practical contribution to Coffee Shop Lingkar's management in improving employee loyalty through developing a participatory and transformational leadership style, providing continuous motivation, and creating a conducive work environment.